Femtoscopy with strange particles in pPb collisions at √sNN = 8.16 TeV at CMS - Lemos, Dener de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Femtoscopy is a powerful method for probing the space-time dimensions of particle emitting sources created in high energy collisions through particle correlations. Such correlations are sensitive to the quantum statistics obeyed by the identical particles involved, as well as to the strong interaction felt by hadrons, for both identical or non-identical pairs. This work presents results of femtoscopic correlations for all pair combinations of K0S, Λ and Λbar with data from the LHC Run 2 collected by the Compact Muon Solenoid (CMS) experiment in proton-lead collisions at √sNN = 8.16 TeV. Detailed studies of the femtoscopic correlations are performed employing the single ratio technique of particles from the same event to those from different events, together with other data driven methods employed to extract the desired information. The Lednicky-Lyubolshitz model is used to parametrize the strong interactions, allowing to obtain the scattering observables, as well as the size of the particle emitting region. The present analysis is performed using samples of events in a wide range of charged particle multiplicities and pair average transverse momenta. This is the first femtoscopic correlation measurement of K0SK0S in pPb collisions and the first ΛΛbar and K0SΛ ⊕ K0SΛbar correlation results in small colliding systems. In the study of the strong interactions using femtoscopy of baryon-antibaryon pair, an anticorrelation is observed, whereas the opposite behavior is seen in the case of baryon-baryon pair correlations, both observations being consistent with previous measurements. Furthermore, the baryon-antibaryon scattering parameters showed an independent behavior with respect to charged particle multiplicity.

A femtoscopia é um método utilizado para investigar as dimensões espaço-temporais da fonte emissora de partículas criada em colisões a altas energias, através de correlações entre elas. Tais correlações são sensíveis à estatística quântica obedecida pelas partículas idênticas envolvidas, assim como à interação forte sentida pelos hádrons, sejam eles idênticos ou não-idênticos. O presente trabalho apresenta resultados de correlações femtoscópicas de partículas para todas as combinações de pares de K0S, Λ e Λbar, com dados do Run 2 do LHC coletados pelo experimento Compact Muon Solenoid (CMS) em colisões próton-chumbo (pPb) a √sNN = 8.16 TeV. Neste trabalho, as correlações femtoscópicas são me- didas utilizando a técnica de single ratio para partículas do mesmo evento em relação a partículas de eventos diferentes, juntamente com outros métodos baseados nos dados, empregados para extrair as informações desejadas. O modelo Lednicky-Lyubolshitz é aplicado para parametrizar as interações fortes entre há- drons, permitindo obter tanto os observáveis de espalhamento, quanto o tamanho da fonte emissora de partículas. A presente análise é realizada usando even- tos com ampla variação de multiplicidades de partículas carregadas e momento transversal médio do par. Esse é a primeira medida de correlações femtoscópica de K0SK0S em colisões pPb e a primeira de correlações de ΛΛbar e K0SΛ ⊕ K0SΛbar em colisões de sistemas pequenos. No estudo das fortes utilizando a femtoscopia de pares bárion-antibárion, observa-se uma anticorrelação, enquanto o comportamento oposto é visto no caso de correlações de pares bárion-bárion, sendo ambos consistentes com resultados de outros experimentos. Além disso, os parâmetros de espalhamento para pares bárion-antibárion mostraram independência em relação à multiplicidade de partículas carregadas.
Femtoscopia com partículas estranhas em colisões pPb a √sNN = 8.16 TeV no CMS
Keywords: Femtoscopy; Strange particles; Strong interaction; Small colliding systems; Femtoscopia; Partículas estranhas; Interação forte; Sistemas pequenos de colisão